High-content red mud-based filling material as well as preparation method and application thereof

By preparing high-dose red mud-based filling materials and using composite acid exciters to stimulate red mud, the problems of low resource utilization rate of red mud and insufficient strength of filling materials are solved, and efficient filling and environmental friendliness are achieved in the high sulfate goaf area.

CN119841598APending Publication Date: 2025-04-18GUIZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510083013.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The comprehensive utilization rate of red mud is low, and traditional filling materials are difficult to meet the strength requirements of high sulfate goaf filling materials, and there is a risk of environmental pollution.

Method used

A high-dose red mud-based filling material is used to mix red mud, fly ash, composite acid exciter and water to form a composite material, and then mix it with cement to prepare a filling material with high strength and good fluidity.

Benefits of technology

It has achieved the formation of high-strength filler in the high sulfate goaf, which can effectively seal strong acidic sewage, meet the filling design requirements, and has good environmental friendliness and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841598A_ABST
    Figure CN119841598A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of filling materials, and provides a high-dosage red mud-based filling material as well as a preparation method and application thereof. The high-dosage red mud-based filling material comprises the following components in parts by mass: 100 parts of red mud, 6-14 parts of fly ash, 8-16 parts of cement, 3-5 parts of a composite acid activator and 60-95 parts of water, the composite acid activator is a boric acid and citric acid compounded activator or a boric acid and calcium chloride compounded activator. The high-doping-amount red mud-based filling material can be rapidly solidified in a high-sulfate goaf, has high strength, meets the filling requirement of the high-sulfate goaf, also has good fluidity and environmental friendliness, and has a good filling effect when being applied to filling of the high-sulfate goaf. Strong-acid sewage in the high-sulfate goaf can be effectively blocked, and the method has a good ecological environment restoration effect and remarkable economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of filling materials, and in particular to a high-dosage red mud-based filling material and a preparation method and application thereof. Background Art

[0002] Red mud is a strong alkaline solid waste generated during the production of alumina. Its harmless treatment and comprehensive resource utilization are currently global problems that restrict the green and healthy development of the alumina industry. Red mud contains a large amount of iron oxide, aluminum oxide, silicon dioxide, calcium oxide and other components; due to its unique chemical composition and physical properties, it is difficult to use directly. Traditional treatment methods such as stacking or landfilling not only occupy a large amount of land resources, but may also cause soil and water pollution and radioactive pollution. In addition, the comprehensive resource utilization rate of red mud is low, which has become one of the important bottlenecks restricting the green and healthy development of the alumina industry.

[0003] Some existing coal mine goafs have highly acidic water, with sulfate content > 4500mg / L, which has a large pollution load. These highly acidic sewage can enter the surrounding watershed through underground karst channels and mine openings, thereby polluting the surrounding environment. Under these conditions, traditional cement slurry (paste) filling materials are difficult to gel and solidify and form strength, and the filling body has poor corrosion resistance and cannot meet the requirements of the design strength of filling in high sulfate goafs.

[0004] In summary, there is an urgent need to provide an environmentally friendly filling material that can simultaneously utilize red mud as a resource and meet the filling strength requirements of high-sulfate goaf areas, so as to improve the resource utilization rate of red mud and improve the strength of the filling material in high-sulfate goaf areas. Summary of the invention

[0005] In view of this, the present invention provides a high-doped red mud-based filling material and a preparation method and application thereof, in order to solve the problem that the comprehensive utilization rate of red mud resources is low and the existing filling materials are difficult to meet the strength requirements of filling materials in acidic, high-sulfate and high-water goaf areas.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention provides a high-dosage red mud-based filling material, comprising the following components in parts by weight:

[0008] 100 parts of red mud, 6-14 parts of fly ash, 8-16 parts of cement, 3-5 parts of composite acid activator, and 60-95 parts of water; the composite acid activator is a composite activator of boric acid and citric acid or a composite activator of boric acid and calcium chloride.

[0009] Preferably, the mass ratio of the boric acid to the citric acid is 0.4 to 0.6; the mass ratio of the boric acid to the calcium chloride is 0.1 to 0.4.

[0010] Preferably, the particle size of the red mud is 200-300 mesh; the particle size of the fly ash is 150-250 mesh.

[0011] The present invention also provides a method for preparing a high-dosage red mud-based filling material, comprising the following steps:

[0012] 1) mixing red mud, fly ash, composite acid activator and water, reacting to obtain a composite material;

[0013] 2) The composite material is mixed with cement to react and obtain a high-content red mud-based filling material.

[0014] Preferably, the reaction time in step 1) is 5 to 10 minutes.

[0015] Preferably, the reaction time in step 2) is 3 to 8 minutes.

[0016] The present invention also provides an application of a high-dosage red mud-based filling material prepared by the above-mentioned preparation method of a high-dosage red mud-based filling material in filling a high-sulfate goaf area.

[0017] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention uses a composite acid activator to activate red mud, and prepares a high-strength, environmentally friendly filling material. The compressive strength of the material can reach 4.36MPa after curing for 28 days in simulated mine acid wastewater, and the strength will not decrease with the increase of curing time. The initial setting time is about 5h, the final setting time is about 12h, the fluidity is good, and the filling requirements of high-sulfate goaf areas can be met. It can solidify quickly in high-sulfate goaf areas, and solves the problem that the existing traditional filling materials are difficult to solidify in high-sulfate goaf areas. At the same time, the leaching toxicity of the high-doped red mud-based filling material of the present invention meets the requirements of Class IV of the surface water environmental quality standard (GB3838-2002), and is environmentally friendly. When the material is applied to the filling of high-sulfate goaf areas, it can effectively block the strong acidic sewage in the high-sulfate goaf areas, and has good ecological environment restoration effects and significant economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0020] Figure 1 This is the XRD pattern of the high-dosage red mud-based filling material in Example 3 after curing for 28 days in simulated mine acid wastewater (the horizontal coordinate is angle / °, and the vertical coordinate is intensity / au);

[0021] Figure 2 This is a SEM image of the high-dosage red mud-based filling material in Example 3 after curing for 28 days in simulated mine acid wastewater;

[0022] Figure 3 This is a state diagram of the fly ash-based filling material in Comparative Example 1 after curing for 7 days in simulated mine acidic wastewater. DETAILED DESCRIPTION

[0023] The present invention provides a high-dosage red mud-based filling material, comprising the following components in parts by weight:

[0024] 100 parts of red mud, 6-14 parts of fly ash, 8-16 parts of cement, 3-5 parts of composite acid activator, and 60-95 parts of water; the composite acid activator is a composite activator of boric acid and citric acid or a composite activator of boric acid and calcium chloride, preferably a composite activator of boric acid and citric acid.

[0025] In the present invention, the fly ash is preferably 8 to 12 parts, more preferably 10 parts; the cement is preferably 9 to 13 parts, more preferably 12 parts; the composite acid activator is preferably 3.5 to 4.5 parts, more preferably 4 parts; the water is preferably 75 to 85 parts, more preferably 80 parts.

[0026] In the present invention, the red mud is preferably taken from Qingzhen Guang Aluminum Group Co., Ltd., and its chemical composition is shown in Table 1 below.

[0027] Table 1 Chemical composition of red mud

[0028]

[0029]

[0030] In the present invention, the fly ash is preferably taken from the primary ash (grade III fly ash) of Qingzhen Guang Aluminum Group Co., Ltd.

[0031] In the present invention, the cement is preferably purchased from Guiyang Conch Panjiang Cement Co., Ltd. Conch brand composite silicate cement (P·C 42.5).

[0032] In the present invention, the addition of the composite acid activator can stably increase the strength of the high-dosage red mud-based filling material.

[0033] In the present invention, the mass ratio of the boric acid to the citric acid is 0.4 to 0.6, preferably 0.45 to 0.55, more preferably 0.5; the mass ratio of the boric acid to the calcium chloride is 0.1 to 0.4, preferably 0.2 to 0.3, more preferably 0.25.

[0034] In the present invention, the particle size of the red mud is 200-300 mesh, preferably 220-280 mesh, and more preferably 250 mesh; the particle size of the fly ash is 150-250 mesh, preferably 180-220 mesh, and more preferably 200 mesh.

[0035] The present invention also provides a method for preparing the above-mentioned high-dosage red mud-based filling material, comprising the following steps:

[0036] 1) mixing red mud, fly ash, composite acid activator and water, reacting to obtain a composite material;

[0037] 2) The composite material is mixed with cement to react and obtain a high-content red mud-based filling material.

[0038] In the present invention, the reaction time in step 1) is 5 to 10 minutes, preferably 6 to 8 minutes, and more preferably 7 minutes.

[0039] In the present invention, the reaction time in step 2) is 3 to 8 minutes, preferably 5 to 7 minutes, and more preferably 6 minutes.

[0040] The present invention also provides an application of a high-dosage red mud-based filling material prepared by the above-mentioned preparation method of a high-dosage red mud-based filling material in filling a high-sulfate goaf area.

[0041] In the present invention, a strength prediction model based on 100 parts of red mud is also provided, as shown in Formula 1:

[0042] Y=0.19A-0.0966A 2 +0.023A 3 +0.28B-0.049B 2 +0.00209B 3 +1.88C-0.17C 2 +0.

[0043] 00544C 3 +61.58D-165.98D 2 +97.95D 3 (1)

[0044] In the formula, Y is the compressive strength after 28 days; A is the mass fraction of the composite acid activator; B is the mass fraction of fly ash; C is the mass fraction of cement; and D is the percentage of water. The correlation coefficient of the strength prediction model is 0.992.

[0045] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0046] Example 1

[0047] 1) First, a composite acid activator is prepared, and boric acid and citric acid are mixed at a mass ratio of 0.5 to obtain a composite acid activator for standby use; then 100 parts of red mud (taken from Qingzhen Guang Aluminum Group Co., Ltd., the chemical composition is shown in Table 1, and the particle size is 250 mesh) and 10 parts of fly ash (taken from Qingzhen Guang Aluminum Group Co., Ltd., Grade III fly ash, with a particle size of 200 mesh) are mixed uniformly in a stirring pot, and then 5 parts of the composite acid activator are added, and then 80 parts of water are added, and the mixture is stirred while adding water, and the reaction is carried out for 7 minutes to obtain a composite material;

[0048] 2) The composite material in step 1) was mixed with 12 parts of cement (P·C 42.5) and reacted for 6 minutes to obtain a high-content red mud-based filling material.

[0049] Experimental Example 1

[0050] The high-dosage red mud-based filling material prepared in Example 1 was placed in a 40 mm × 160 mm stainless steel mold, then placed on a vibration table for 5 min, and demolded after standing for 24 h to obtain a sample, which was placed in a plastic water tank filled with simulated mine acid wastewater for natural curing. When the curing time was 3d, 7d, 14d, and 28d, the samples were taken out for compressive and flexural strength tests. Among them, the strength test was carried out according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021).

[0051] The simulated acid mine wastewater is prepared from ferrous sulfate, sulfuric acid and water, with an iron content of 3195 mg / L and a pH of 2.8. The test results are shown in Table 2 below.

[0052] Table 2 Strength of high-dosage red mud-based filling materials in simulated mine acid wastewater

[0053]

[0054] It can be seen from Table 2 that with the increase of curing time, the strength of the filling material shows an increasing trend, that is, the high-dosage red mud-based filling material provided by the present invention has higher strength and can meet the filling requirements of high-sulfate goaf areas.

[0055] Example 2

[0056] The difference between Example 2 and Example 1 is that the amount of water added is 75 parts.

[0057] Example 3

[0058] The only difference between Example 3 and Example 2 is that the amount of cement added is 14 parts.

[0059] Example 4

[0060] The only difference between Example 4 and Example 2 is that the amount of cement added is 16 parts.

[0061] Experimental Example 2

[0062] The setting time of the high-dosage red mud-based filling materials prepared in Examples 2 to 4 was tested. The specific test process was carried out in accordance with the "Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency". The test results are shown in Table 3 below.

[0063] Table 3 Initial and final setting time of high-content red mud-based filling materials

[0064] Initial setting time / h Final setting time / h Example 2 6.5 14.5 Example 3 5.1 12.2 Example 4 4.5 10.5

[0065] It can be seen from Table 3 that the initial setting time and final setting time of the high-dosage red mud-based filling material prepared by the present invention are shortened with the increase of cement addition, and the initial setting time and final setting time will neither affect the transportation and pouring of the concrete mixture nor the construction progress of the concrete project, and the application range is very wide.

[0066] Experimental Example 3

[0067] The high-content red mud-based filling material prepared in Example 3 was naturally cured using the same curing method as in Experimental Example 1. When the curing time was 3d, 7d, 14d and 28d, samples were taken out for compressive and flexural strength tests. The strength test was carried out in accordance with the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The test results are shown in Table 4 below.

[0068] Table 4 Strength of high-dosage red mud-based filling materials in simulated acid mine wastewater

[0069]

[0070]

[0071] It can be seen from Table 4 that when the activator composed of boric acid and citric acid provided by the present invention is used as the activator and the cement addition amount is 14 parts, with the increase of oxidation time, the compressive strength and flexural strength both gradually increase, and the compressive strength after 28 days can reach 3.9 MPa. There is no strength attenuation with the increase of curing time. Therefore, the red mud-based filling material prepared with the activator provided by the present invention is very suitable for filling high sulfate goaf areas.

[0072] The red mud-based filling material samples after curing for 28 days were taken for phase (XRD) and electron microscopy (SEM) analysis. The analysis results are as follows: Figure 1 and Figure 2 As shown. Figure 1 It can be seen that when the cement addition amount is 14 parts, the phases of the filling material are SiO2, CaCO3, Ca3Al2(SiO4)(OH)8, 3NaAlSiO4·Na2CO3 and Fe 10.56 H 0.36 O 18.00 The sodium mainly exists in the stable nepheline phase 3NaAlSiO4·Na2CO3, which is the reason for fixing the sodium in the red mud and ensuring that the filling material does not show strength decay during the subsequent filling process. Figure 2 It can be seen that adding appropriate cement is conducive to forming a dense network structure, thereby increasing the strength of the filling material.

[0073] XRF analysis was performed on the red mud-based filling material samples after curing for 28 days in this experimental example, and the results are shown in Table 5 below.

[0074] Table 5 XRF analysis results of high-dosage red mud-based filling materials

[0075] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO <![CDATA[Fe2O3]]> <![CDATA[SO3]]> <![CDATA[TiO2]]> <![CDATA[Na2O]]> <![CDATA[K2O]]> MgO <![CDATA[P2O5]]> content / % 31.64 22.82 22.66 9.32 4.27 3.11 2.48 1.68 1.26 0.214

[0076] It can be seen from Table 5 that the iron content in the filling material is slightly lower than that in the red mud slag, which indicates that the iron salts in the high-sulfate goaf did not migrate into the filling material. The reduction in sodium ions may be due to the migration of sodium ions into the aqueous solution before solidification. After solidification, there is still 2.5% sodium in the filling material in the form of 3NaAlSiO4·Na2CO3.

[0077] Experimental Example 4

[0078] The samples in Experimental Example 3 after curing for 28 days were subjected to leaching toxicity analysis, and the leachate was extracted by the horizontal oscillation method and the nitric acid and sulfuric acid method. Among them, the horizontal oscillation method was used to extract the filling material leachate according to the "Solid Waste Leaching Toxicity Leaching Method Horizontal Oscillation Method" (HJ557-2010), and then the main elements were determined according to the general industrial solid waste identification method, and the surface water standard was benchmarked; the nitric acid and sulfuric acid method was used to extract the filling material leachate according to the "Solid Waste Leaching Toxicity Leaching Method Nitric Acid and Sulfuric Acid Method" (HJ229-2007), and the toxicity was identified according to the "Hazardous Waste Identification Standard Leaching Toxicity Identification" (GB5085.3-2007).

[0079] The results of toxicity analysis of the leachate extracted from the high-dosage red mud-based filling material samples after 28 days of curing using the horizontal oscillation method are shown in Table 6 below, where ND stands for not detected.

[0080] Table 6 Results of leaching toxicity analysis of red mud-based filling material samples by horizontal oscillation method

[0081]

[0082] It can be seen from Table 6 that the leaching toxicity of the red mud-based filling material prepared using the activator provided by the present invention meets the requirements of Class IV of the Surface Water Environmental Quality Standard (GB3838-2002).

[0083] The results of toxicity analysis of the leachate extracted from the high-dosage red mud-based filling material samples after 28 days of curing using the nitric acid and sulfuric acid method are shown in Table 7 below, where ND stands for not detected.

[0084] Table 7 Toxicity analysis results of red mud-based filling material samples leached by nitric acid and sulfuric acid method

[0085]

[0086]

[0087] It can be seen from Table 7 that the red mud-based filling material prepared by the activator provided by the present invention is not classified as hazardous waste according to the hazardous waste identification standard (GB5085.3-2007).

[0088] Example 5

[0089] The only difference between Example 5 and Example 1 is that the amount of cement added is 14 parts.

[0090] Example 6

[0091] The only difference between Example 6 and Example 1 is that the amount of cement added is 16 parts.

[0092] Experimental Example 5

[0093] The high-content red mud-based filling materials prepared in Examples 1, 5, and 6 were tested for fluidity. The specific test method was carried out in accordance with the "Method for Determination of Fluidity of Cement Mortar" (GBT2419-2005). The test results are shown in Table 8 below.

[0094] Table 8 Fluidity of high-content red mud-based filling materials

[0095] Cement addition amount / part Diameter 1 / cm Diameter 2 / cm Average value / cm Example 1 12 28 29 28.5 Example 5 14 23.4 23.5 23.45 Example 6 16 21.2 21.3 21.25

[0096] It can be seen from Table 8 that the high-dosage red mud-based filling material provided by the present invention meets the F4 level of fluidity of concrete, has ultra-high fluidity, and can well meet the filling requirements.

[0097] Example 7

[0098] The difference between this embodiment 7 and embodiment 1 is that the amount of water added is 60 parts.

[0099] Experimental Example 6

[0100] The slump test was performed on the high-content red mud-based filling materials prepared in Examples 1, 5, and 7. The specific test method was carried out in accordance with the "Standard for Test Methods for Performance of Ordinary Concrete Mixtures" (GB / T50080-2016). The test results are shown in Table 9 below.

[0101] Table 9 Slump of high-content red mud-based filling materials

[0102] Cement addition amount / part Amount of water added / portion Reading / cm Example 1 12 80 0 Example 5 14 80 22 Example 7 12 60 24

[0103] It can be seen from Table 9 that the high-content red mud-based filling material of the present invention has good slump parameters, which can ensure that the filling material remains intact after being filled into the acidic high-sulfate goaf.

[0104] Example 8

[0105] The only difference between Example 8 and Example 1 is that the amount of water added is 85 parts.

[0106] Example 9

[0107] The difference between Example 9 and Example 1 is that the amount of water added is 90 parts.

[0108] Example 10

[0109] The difference between Example 10 and Example 1 is that the amount of water added is 95 parts.

[0110] Experimental Example 7

[0111] The high-content red mud-based filling materials prepared in Examples 2, 8 to 10 were naturally cured by the same curing method as in Experimental Example 1. When the curing time was 3d, 7d, 14d and 28d, samples were taken out for compressive and flexural strength tests. Among them, the strength test was carried out according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The test results are shown in Table 10 below.

[0112] Table 10 Strength of high-dosage red mud-based filling materials with different water addition amounts in simulated acid mine wastewater

[0113]

[0114]

[0115] It can be seen from Table 10 that the high-dosage red mud-based filling materials prepared in Examples 2 and 8 to 10 of the present invention can meet the filling requirements of 0.6Mpa after curing in simulated mine acid wastewater for 3 days, and the strength basically shows an increasing trend with time. As the amount of water added increases, the strength of the filling material gradually decreases. When the amount of water added is less than 85 parts, this change trend is more obvious, which may be related to its gelling process. After adding too much water, part of the cement gelling effect fails.

[0116] Embodiment 11

[0117] The only difference between Example 11 and Example 2 is that the added amount of the composite acid activator is 3 parts.

[0118] Example 12

[0119] The only difference between Example 12 and Example 11 is that the amount of cement added is 8 parts.

[0120] Embodiment 13

[0121] The only difference between Example 13 and Example 11 is that the amount of cement added is 10 parts.

[0122] Embodiment 14

[0123] The only difference between Example 14 and Example 11 is that the amount of cement added is 14 parts.

[0124] Embodiment 15

[0125] The only difference between Example 15 and Example 11 is that the amount of cement added is 16 parts.

[0126] Experimental Example 8

[0127] The high-content red mud-based filling materials prepared in Examples 11 to 15 were naturally cured using the same curing method as in Experimental Example 1. When the curing time was 3d, 7d, 14d and 28d, samples were taken out for compressive and flexural strength tests. The strength test was carried out in accordance with the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The test results are shown in Table 11 below.

[0128] Table 11 Strength of high-content red mud-based filling materials with different cement contents in simulated acid mine wastewater

[0129]

[0130]

[0131] It can be seen from Table 11 that when the addition amount of the composite acid activator is 3 parts, as the amount of cement added increases, the compressive and flexural strengths gradually increase. As the maintenance time increases, the compressive and flexural strengths also gradually increase. When the amount of cement added is greater than 12 parts, the 28-day strength is greater than 2.04Mpa, which can meet the needs of industrial production.

[0132] Example 16

[0133] The only difference between Example 16 and Example 2 is that the amount of cement added is 8 parts.

[0134] Embodiment 17

[0135] The only difference between Example 17 and Example 2 is that the amount of cement added is 10 parts.

[0136] Experimental Example 9

[0137] The high-content red mud-based filling materials prepared in Examples 3-4 and Examples 16-17 were naturally cured using the same curing method as in Experimental Example 1. When the curing time was 3d, 7d, 14d and 28d, samples were taken out for compressive and flexural strength tests. The strength test was carried out in accordance with the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The test results are shown in Table 12 below.

[0138] Table 12 Strength of high-content red mud-based filling materials with different cement contents in simulated acid mine wastewater

[0139]

[0140]

[0141] It can be seen from Table 12 that with the increase of curing time, the strength of red mud-based filling materials shows an increasing trend. With the increase of cement addition, the strength of red mud-based filling materials also gradually increases. When the cement addition is greater than 12 parts, this change trend is more obvious.

[0142] Comparative Example 1

[0143] The conventional fly ash-based filling material is naturally cured in simulated mine acid wastewater. The preparation method of the fly ash-based filling material is as follows: 30 parts of 425# cement and 70 parts of fly ash are mixed, and then 60 parts of tap water are added to obtain the fly ash-based filling material.

[0144] The fly ash-based filling material was placed in a 40 mm × 160 mm stainless steel mold, and then placed on a vibration table for 5 min. After standing for 48 h, it was demoulded and placed in a plastic tank filled with simulated mine acid wastewater (same as in Experimental Example 1) for natural curing. The state of the fly ash-based filling material after 7 days was as follows: Figure 3 As shown, from Figure 3 It can be clearly seen that fly ash-based filling materials are difficult to solidify in simulated mine acid wastewater. The initial setting time of fly ash-based filling materials is greater than 28 hours. After demoulding for 48 hours and curing in simulated mine wastewater for 7 days, the samples cracked and had extremely low strength, which obviously could not meet the filling requirements of high sulfate goaf areas.

[0145] Comparative Example 2

[0146] The only difference between Comparative Example 2 and Example 1 is that no composite acid activator is added.

[0147] Comparative Example 3

[0148] The difference between Comparative Example 3 and Comparative Example 2 is that the amount of cement added is 14 parts.

[0149] Comparative Example 4

[0150] The difference between Comparative Example 4 and Comparative Example 2 is that the amount of cement added is 16 parts.

[0151] Experimental Example 10

[0152] The high-content red mud-based filling materials prepared in Comparative Examples 2 to 4 were naturally cured using the same curing method as in Experimental Example 1. When the curing time was 3d, 7d, 14d and 28d, samples were taken out for compressive and flexural strength tests. The strength test was carried out in accordance with the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The test results are shown in Table 13 below.

[0153] Table 13 Strength of high-dosage red mud-based filling materials in simulated acid mine wastewater

[0154]

[0155] It can be seen from Table 13 that the strength of the high-dosage red mud-based filling material prepared by treating the red mud without adding a composite acid activator is greatly reduced, and with the increase of maintenance time, there is a trend of first increasing and then decreasing. Even increasing the amount of cement added cannot change the above trend, which is not allowed in actual engineering applications. This material is obviously not suitable for filling high-sulfate goaf areas.

[0156] Comparative Example 5

[0157] The difference between Comparative Example 5 and Comparative Example 2 is that the amount of fly ash added is 12 parts.

[0158] Comparative Example 6

[0159] The only difference between Comparative Example 6 and Comparative Example 2 is that the amount of fly ash added is 14 parts.

[0160] Experimental Example 11

[0161] The high-content red mud-based filling materials prepared in Comparative Examples 5 to 6 were naturally cured using the same curing method as in Experimental Example 1. When the curing time was 3d, 7d, 14d and 28d, samples were taken out for compressive and flexural strength tests. The strength test was carried out in accordance with the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The test results are shown in Table 14 below.

[0162] Table 14 Strength of high-dosage red mud-based filling materials in simulated mine acid wastewater

[0163]

[0164] It can be seen from Table 14 that the high-dosage red mud-based filling material prepared by treating red mud without adding composite acid activator shows a downward trend in compressive strength and flexural strength as the amount of fly ash added increases. Moreover, as the maintenance time increases, the strength of the filling material still shows a trend of first increasing and then decreasing. It is obviously not suitable for filling high-sulfate goaf areas.

[0165] The strength prediction model calculated based on 100 parts of red mud was used to predict the 28-day compressive strength of high-dosage red mud-based filling materials, and the estimated value was obtained. The prediction results are shown in Table 15 below.

[0166] Among them, the strength prediction model calculated with the red mud dosage as 100 parts is shown in Formula 1:

[0167] Y=0.19A-0.0966A 2 +0.023A 3+0.28B-0.049B 2 +0.00209B 3 +1.88C-0.17C 2 +0.

[0168] 00544C 3 +61.58D-165.98D 2 +97.95D 3 (1)

[0169] In the formula, Y is the compressive strength after 28 days; A is the mass fraction of the composite acid activator; B is the mass fraction of fly ash; C is the mass fraction of cement; and D is the percentage of water. The correlation coefficient of the strength prediction model is 0.992.

[0170] Table 15 Measured and estimated values ​​of 28-day compressive strength of high-content red mud-based filling materials

[0171]

[0172]

[0173] It can be seen from Table 15 that the strength prediction model provided by the present invention accurately predicts the 28-day compressive strength of high-dosage red mud-based filling materials, indicating that the strength prediction model is reasonably designed, has a high degree of fit, a small error, and has broad application prospects.

[0174] In summary, traditional fly ash-based filling materials are difficult to solidify in simulated mine acidic wastewater, and they cannot meet the requirements for filling high-sulfate goafs. Moreover, if the composite acid stimulator provided by the present invention is not used to stimulate the red mud, the strength of the obtained filling material in the simulated mine acidic wastewater will decrease with time, and it cannot meet the requirements for filling high-sulfate goafs. After the red mud is stimulated by the composite acid stimulator provided by the present invention, the 28-day compressive strength of the obtained filling material can reach up to 4.36Mpa, which can not only meet the requirements for filling high-sulfate goafs, but also solve the technical difficulties of filling acidic high-sulfate goafs, effectively block the strong acidic sewage in high-sulfate goafs, and have good fluidity and environmental friendliness, good ecological environment restoration effect and significant economic benefits.

[0175] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-dosage red mud-based filling material, characterized in that: The composition includes the following components in parts by weight: 100 parts of red mud, 6-14 parts of fly ash, 8-16 parts of cement, 3-5 parts of composite acid activator, 60-95 parts of water; The composite acid stimulator is a composite stimulator of boric acid and citric acid or a composite stimulator of boric acid and calcium chloride.

2. A high-dosage red mud-based filling material according to claim 1, characterized in that: The mass ratio of boric acid to citric acid is 0.4 to 0.6; The mass ratio of the boric acid to calcium chloride is 0.1 to 0.

4.

3. A high-dosage red mud-based filling material according to claim 2, characterized in that: The particle size of the red mud is 200 to 300 meshes; The particle size of the fly ash is 150-250 meshes.

4. The method for preparing a high-dosage red mud-based filling material according to any one of claims 1 to 3, characterized in that: The steps include: 1) mixing red mud, fly ash, composite acid activator and water, reacting to obtain a composite material; 2) The composite material is mixed with cement to react and obtain a high-content red mud-based filling material.

5. The method for preparing a high-dosage red mud-based filling material according to claim 4, characterized in that: The reaction time in step 1) is 5 to 10 minutes.

6. The method for preparing a high-dosage red mud-based filling material according to claim 5, characterized in that: The reaction time in step 2) is 3 to 8 minutes.

7. Use of the high-dosage red mud-based filling material prepared by the method for preparing a high-dosage red mud-based filling material as described in any one of claims 4 to 6 in filling high-sulfate goaf areas.

Citation Information

Cited By

  • Organic-inorganic acid excited geopolymer and preparation method thereof

    CN120349126A